PENGHIJAUAN SEBAGAI SALAH SATU SARANA MEWUJUDKAN KOTA BERWAWASAN LINGKUNGAN - Susatyo Adhi Pramono (Fakultas Teknik Universitas Wijayakusuma Purwokerto, 2007)
AbstractÂ Development of town has altered availibility open green scape to become development scape. As a result town dweller cannot enjoy open green scape equaly. Reforestation is effort for environmental settlement by using plants as matter in essence. With reforestation town is expected can have lung to return for its dweller.Keyword: development of town, reforestation.